Inovasi Terasi berbasis Bycatch Upaya Peningkatan Daya saing Produk Pohlaksar Camar Laut - Rahmawati Rahmawati; Nabila Ukhty; Arrazy Elba Ridha; Andayani (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
Kelompok Pengolah dan Pemasar (Poklahsar) Camar Laut has considerable potential in developing fisheries-based enterprises in Suak Indra Puri Village, West Aceh Regency. Previously, shrimp paste production relied solely on rebon shrimp as the primary raw material, which is seasonal in nature and often leads to limited availability. This dependence has constrained the group’s production capacity and hindered business optimization. To address this issue, a community service program was implemented by introducing the utilization of bycatch fish as an alternative raw material for shrimp paste production. The program applied a Asset Based Community Development (ABCD), which involves women's group members actively utilizing existing potential. The outcomes indicate significant improvements in the group’s capacity, particularly in knowledge, technical skills, and the ability to create innovative products based on local resources. The innovations in bycatch-based shrimp paste also provide opportunities for more sustainable business diversification. These efforts are expected to enhance the group’s economic resilience, increase product competitiveness, and contribute to household welfare as well as local economic growth.